Use of Personal Protective Equipment and Length of Work as Risk Factors for Occupational Contact Dermatitis on the Hands of Woodworkers - Anggelina Aiyoslla Nabilla Putu Pratomo; Ratih Pramuningtyas; Flora Ramona Sigit Prakoeswa; Yusuf Alam Romadhon (HM Publisher, 2023)
Background: Occupational contact dermatitis (OCD) is an inflammatory response caused by contact with allergens or irritants in the work environment, and this disease is most often found as an occupational disease. Personal protective equipment (PPE) is a safety tool that must be used by workers to protect the body from possible potential hazards in the workplace. Construction workers, woodworkers, batik workers, and farmers can take preventive measures to avoid the occurrence of OCD. This study aimed to determine the relationship between the length of work and the use of PPE on the incidence of OCD on the hands of woodworkers in Serenan, Klaten. Methods: Cross-sectional analytic observational study. A total of 30 research subjects participated in this study. The research subjects were woodworkers in Serenan, Klaten, Indonesia. Univariate and bivariate data analysis was carried out with the help of the SPSS program. Results: The majority of research subjects with OCD have worked for more than 3 years and do not use PPE. Studies show that there is a relationship between the length of work and the use of PPE with the incidence of OCD. Conclusion: There is a significant relationship between the length of work and the use of PPE on the incidence of OCD on the hands of woodworkers in Serenan, Klaten, Indonesia.